Integrated PJBL-PBL Management: Strengthening Character Values in Vocational Education in Bandung City - Iqbal Hilman; Ahmad Sukandar (UIN Sunan Gunung Djati Bandung, 2026)
This study addresses the importance of strengthening students’ character in the global era, when conventional learning often fails to integrate cognition and values. It examines the planning, implementation, and evaluation of a learning model combining Project-Based Learning and Problem-Based Learning, and its implications for character values in vocational high schools. Using a qualitative multi-site case study at SMK Negeri 12 and SMK Vijaya Kusuma, Bandung, the study involved teachers and students through observation, interviews, and documentation. The findings show that the model was implemented systematically through relevant projects/problems, dynamic group organization, and authentic assessment, with Islamic Religious Education teachers playing a key role as character facilitators. This approach improved students’ independence, collaboration, creativity, and responsibility through active engagement in real-world problem-solving and work production. The study concludes that the combined model is effective and relevant for vocational education because it strengthens both vocational competence and character formation.